Angioembolization in massive hemoptysis for a patient with acute coronary syndrome and history of hydatid cyst. Issue 5 (May 2021) - Seyyedi, Seyed Reza; Sadr, Makan; Chitsazan, Mandana; Abedini, Atefeh; Sharif-Kashani, Babak
Abstract: Cystic echinococcosis (CE) or hydatid disease is a zoonosis caused by ingestion of the eggs of the tapeworm Echinococcus granulosus . Larger cysts can cause symptoms by compressing surrounding tissues. Large cysts can also rupture and cause sudden onset of cough, fever, hypersensitivity reactions, and massive hemoptysis. We report a case of hydatid cyst, which caused massive hemoptysis after an urgent percutaneous coronary intervention and was successfully controlled with bronchial artery embolization. <Learning objective: In patients with hydatid cyst, even old lesions, there is a possibility of bleeding and massive hemoptysis after anticoagulation treatment. Bronchial artery embolization is a safe and effective therapy in these situations, when the patient is not a good surgical candidate and the bleeding is life-threatening.>